2021
DOI: 10.1073/pnas.2016806118
|View full text |Cite
|
Sign up to set email alerts
|

A genome-scale CRISPR screen reveals factors regulating Wnt-dependent renewal of mouse gastric epithelial cells

Abstract: An ability to safely harness the powerful regenerative potential of adult stem cells for clinical applications is critically dependent on a comprehensive understanding of the underlying mechanisms regulating their activity. Epithelial organoid cultures accurately recapitulate many features of in vivo stem cell-driven epithelial renewal, providing an excellent ex vivo platform for interrogation of key regulatory mechanisms. Here, we employed a genome-scale clustered, regularly interspaced, short palindromic rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 44 publications
2
28
0
1
Order By: Relevance
“…The organoid culture has enabled us to assess the reponse of intestinal epithelial cells to anti-cancer drugs, growth factors, or inflammatory cytokines and analyze the detailed molecular mechanisms in vitro (Lindemans et al, 2015 ; De Sousa E Melo et al, 2017 ; Kajino-Sakamoto et al, 2021 ). A recent study has performed a genome-scale CRISPR screen to identify genes that regulate Wnt-dependent renewal of gastric epithelial cells and identified Alk, Bclaf3 , and Prkra as Wnt pathway regulators (Murakami et al, 2021 ); the data show that mouse organoids are also useful for stem cell research.…”
Section: Discussionmentioning
confidence: 99%
“…The organoid culture has enabled us to assess the reponse of intestinal epithelial cells to anti-cancer drugs, growth factors, or inflammatory cytokines and analyze the detailed molecular mechanisms in vitro (Lindemans et al, 2015 ; De Sousa E Melo et al, 2017 ; Kajino-Sakamoto et al, 2021 ). A recent study has performed a genome-scale CRISPR screen to identify genes that regulate Wnt-dependent renewal of gastric epithelial cells and identified Alk, Bclaf3 , and Prkra as Wnt pathway regulators (Murakami et al, 2021 ); the data show that mouse organoids are also useful for stem cell research.…”
Section: Discussionmentioning
confidence: 99%
“…Large scale functional genomic studies via genome-wide screens in cancer cell lines have revealed previously unappreciated genetic regulators and accelerated the drug discovery process (Bowden et al, 2020;Doench et al, 2016;Sanjana et al, 2014). CRISPR screens have started to be applied to 3D organoid systems which can more faithfully recapitulate in vivo biological processes (Murakami et al, 2021;Planas-Paz et al, 2019;Ringel et al, 2020), but so far have required large cell numbers to overcome variability. CRISPR interference (CRISPRi) is particularly useful for the generation of homogenous knockdowns to study essential gene function (Gilbert et al, 2014;Mandegar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that different types of genome-wide screens (gene-trap, siRNA and CRISPR) aimed at the identification of new Wnt signaling components yield different hits [32,33]. Importantly, even the most known and robust Wnt signaling regulators were not highly scored in most cases and the top hits widely differ between individual screens [12,[32][33][34][35][36][37][38][39][40]. This observation was previously discussed [32] and it was suggested that distinct screening systems i.e., different libraries or cell lines used, differences in phenotypic scoring, the length of the screen and other factors affecting knockout efficiency influence the screen results.…”
Section: Discussionmentioning
confidence: 99%